RISK FACTORS OF TYPE 2 DIABETES MELLITUS IN THE ELDERLY - Anggraini, Debie; Nabila Jihan Zakiyah (Nusantara Hasana Journal, 2024)
The high incidence of Type 2 diabetes mellitus (DM) in the elderly in Padang is due to several factors, one of which is an unhealthy lifestyle, namely consumption of foods high in fat, so preventive and promotive efforts are needed in the form of early detection of DM risk factors as well as providing education and health education. to the public about matters relating to DM. The increase in the incidence of DM is related to the increase in the elderly population, economic development, decreased consumption of healthy foods, physical activity and obesity, especially central obesity. Elderly is an advanced stage of the life process that shows signs of decreased physical ability to adapt to environmental pressures which will be measured using the Global Physical Activity Questionnaire (GPAQ).